Dynamic Changes of Glycine and Taurine in Corpus Striatum of Rats with Ischemia-reperfusion Injury and Effects of Electroacupuncture - 徐鸣曙 葛林宝 王新辉 徐佳 王志强 崔毅军 (Journal of acupuncture and tuina science, 2009)
Objective To investigate the dynamic changes of glycine (Gly) and taurine (Tau) in corpus striatum of rats with ischemia-reperfusion injury (IRI), and the regulation effect of electroacupuncture on them. Methods Thirty SD rats were randomly divided into sham surgery group, model group, and treatment group. Rats in the sham surgery group were operated without ischemia. Rats in the model group and treatment group were operated to make model of cerebral IRI. The ischemia status lasts 1.5 h, and reperfusion was performed for 3.75 h. Rats in the treatment group were treated with electroacupuncture at Fengchi (GB 20). Neurologic deficit score (NDS) was used to evaluate the rats functions. Microdialysis and High Performance Liquid Chromatography technique were used to detect the changes of Gly and Tau in corpus striatum of rats. Results Contents of Gly and Tau increased at 1.5 h after ischemia. Them decreased to level as same as those rats in the sham surgery group after reperfusion. The content of Gly in the model and treatment group increased again at 2–2.5 h after reperfusion, and then decreased to the same level of the sham surgery group. There was a third increase of Gly content in the treatment group at 2.75 h after reperfusion. Electroacupuncture treatment could delay the decrease of Tau content after reperfusion, and make it increase at 1.5, 2 and 2.75 h after reperfusion. The peak appeared in the last time. NDS in the model and treatment group were more than that in the sham surgery group, and lowered at 5.25 h after surgery. Effects in treatment group was better than that in the model group ( P <0.05). Conclusion IRI makes contents of Gly and Tau in corpus striatum increase at a special time. Electroacupuncture treatment could increase contents of Gly and Tau at a special time after reperfusion, which maybe an important mechanism of protecting effects of electroacupuncture on the brain.